The value of ultrasound measurement of muscle thickness at different sites and shear wave elastography in Parkinson’s disease with sarcopenia: a pilot study - Chen, Minglei; Liu, Xiaofang; Liu, Qiuwan; Ding, Changwei; Zhao, Ping; Zhang, Yingchun; Mao, Chengjie; Liu, Chunfeng (Frontiers in Neuroscience, 2023)
Background Patients with Parkinson’s disease (PD) and sarcopenia often exhibit resilience, frailty, disability, and depression, highlighting the complex and interrelated nature of these conditions. Objective Despite the presence of clinical manifestations of muscle atrophy in both PD and sarcopenia, accurately discerning the coexistence of sarcopenia in PD patients remains a challenging task with significant implications for treatment strategies and prognostic assessments. This study aims to elucidate the specific ultrasonic diagnostic parameters associated with PD accompanied by sarcopenia through a comparative analysis of muscle ultrasound parameters in patients with PD, thereby presenting a novel approach for rapid identification of this condition. Methods A total of 110 participants were enrolled in this study, including patients with PD and control subjects. Demographic data, clinical characteristics, physical performance tests, appendicular skeletal muscle mass index (ASMI), bioelectrical impedance analysis and muscle ultrasound measurements were collected from all participants. The muscle ultrasound measurements encompassed assessments of muscle thickness, pennation angle and shear wave elastography at various anatomical sites. Results Parkinson’s disease patients exhibited decreased muscle strength and physical performance, and increased shear wave elastography value. In PD patients with sarcopenia, body circumference, including calf circumference, mid-arm circumference, Waist-to-Hip Ratio and body mass index (BMI) were all significantly decreased. Biceps brachii muscle thickness (MT) and gastrocnemius MT decreased in PD patients with sarcopenia and low ASMI. Binary logistic regression analysis revealed that male PD patients, BMI and gastrocnemius MT were predictive factors for ASMI in PD patients. Conclusion Biceps brachii MT and gastrocnemius MT are important indicators for distinguishing whether PD patients have sarcopenia. Male patients, low BMI and gastrocnemius MT were identified as valid predictors of low ASMI in PD patients. The findings of this study provide important insights into the use of muscle ultrasound in the diagnosis of PD with sarcopenia.